The rice economies : technology and development in Asian societies - Bray, Francesca (Berkeley ; Los Angeles ; London : University of California Press, 1994)
Wide-ranging both historically and geographically, The Rice Economies brilliantly addresses a subject of abiding interest to anthropologists, economists, and historians as well as those concerned with development issues and Asian studies. It is the first work to formulate a logical, historical dynamic of development in Asia's rice economies up to the present day. The comparison of mechanized Western farming methods with the more labor intensive, less environmentally destructive Asian methods is of value to environmentalists and economists concerned with the need for sustainable development. In a new preface, the author reflects upon the increasing relevance of the concerns of the book to international environmental issues
Chinese dynasties x -- Japanese eras xi -- Eurocentric models of historical change 1 -- An alternative model 5 -- The significance of a model of development for rice economies 5 -- 1 The rice-plant: diversity and intensification 8 -- The origins of Asian rice 8 -- Natural characteristics of rice 11 -- Selection techniques 19 -- 2 Paths of technical development 27 -- Building new fields 28 -- Raising yields 42 -- Labour productivity and the mechanisation question 54 -- 3 Water control 62 -- Water control and institutions: the debate 63 -- A technical classification of water control systems 68 -- Gravity-fed irrigation networks 69 -- Ponds, tanks and reservoirs 71 -- Contour canals 80 -- 'Creek' irrigation 90 -- Pump irrigation schemes 100 -- Patterns of growth and change 105 -- 4 Rice and the wider economy 113 -- 'Skill-oriented' and 'mechanical' technologies 113 -- The specificity of wet-rice agriculture 116 -- Uniformity and systemic change 119 -- Monoculture and markets 124 -- Economic diversification 131 -- Petty commodity production and rural industrialisation 134 -- 5 Development 140 -- Labour and capital 147 -- The historical experience: the predominance of labour and the 'Japanese model' 148 -- Choice of technological inputs 155 -- Capital investment 158 -- Productivity of labour and capital 163 -- Expertise and participation 166 -- 6 Peasant, landlord and state: changes in relations of production 170 -- Conflict, cooperation and control 170 -- Historical changes in relations of production 175 -- 'Feudal' relations and frontier zones 175 -- Smallholder economies: expansion and stagnation 179 -- Egalitarianism or differentiation: the impact of capitalism 182 -- Land and landlessness 185 -- 'Land to the tiller' 190 -- Group farming 193 -- Socialist land reform 194 -- Appendix A The Western model 198 -- Appendix B The historical experience of China 203 -- Appendix C The Japanese experience 210.
Originally published: Oxford; New York : Blackwell, 1986. With a new preface
Includes bibliographical references (pages 228-247) and index
Online resource; title from ebookviewer title page (EBSCOhost, viewed February 16, 2021)
English.
JSTOR
Keywords: Rice trade -- Asia; Rice -- Technological innovations -- Asia; Asia -- Economic conditions -- 1945-; Agriculture -- Economic aspects -- Asia; Riz -- Commerce -- Asie; Riz -- Innovations -- Asie; Asie -- Conditions économiques -- 1945-; Agriculture -- Aspect économique -- Asie; BUSINESS & ECONOMICS -- Industries -- Agribusiness; TECHNOLOGY & ENGINEERING -- Agriculture -- Sustainable Agriculture; HISTORY / Asia / General; Rice -- Technological innovations; Agriculture -- Economic aspects; Economic history; Rice trade; Asia; Rijstbouw; Economische situatie; Azië; Since 1945